Land in the struggles for citizenship in Africa - Moyo, Sam; Tsikata, Dzodzi; Diop, Yakham (Codesria, 2015)
The variety of land questions facing Africa and the divergent strategies proposed to resolve them continue to evoke debates. Increasingly, in response to the enduring problems of land tenure, there are land movements of all shapes and orientations, some reformist and others quite revolutionary in their agenda. However revolutionary, land movements have tended to ignore the land tenure interests of women, pastoralists, youth and Indigenous people. Several of these longstanding and emerging issues in land tenure include the role of the state in land tenure reforms; urban land questions, the nature of land struggles and improvements; and, the impact of land tenure developments on particular social groups and countries. An overarching concern is the extent to which land rights are being commodified, through the conversion of land held under customary tenure systems into marketised systems. The consequences of this include growing land concentration, land tenure insecurities, diminishing access to land by various sections of society, including the poor, women and less dominant ethno-religious groups. This volume brings together different studies on Africa's land questions exploring emerging land issues on the continent in terms of the wider questions of development, citizenship, and democratisation. The chapters discuss the land question through a variety of themes. Some focus on the agrarian aspects of the land questions, while others elucidate the urban dimensions of the land question.